Tracking Carbapenem-Producing Klebsiella pneumoniae Outbreak in an Intensive Care Unit by Whole Genome Sequencing - Chen, Chen; Zhang, Yi; Yu, Sheng-Lei; Zhou, Yang; Yang, Si-Yu; Jin, Jia-Lin; Chen, Shu; Cui, Peng; Wu, Jing; Jiang, Ning; Zhang, Wen-Hong (Frontiers in Cellular and Infection Microbiology, 2019)
Abstract (195 words) The presence of carbapenem-producing Klebsiella pneumoniae (CP-Kp) is a serious threat to the control of nosocomial infections. Plasmid-mediated horizontal transfer of the resistance gene makes it difficult to control hospital-acquired CP- Kp infections. Nine CP- Kp strains were isolated during an outbreak in the intensive care unit of Shanghai Huashan hospital in east China. We conducted a retrospective study to identify the origin and route of transmission of this CP-Kp outbreak. Whole-genome sequencing (WGS) analysis was performed on 9 clinical isolates obtained from 8 patients, and the results were compared to clinical and epidemiological records. All isolates were ST11 CP-Kp. Single-nucleotide polymorphisms and the presence and structure of plasmids indicated that this CP-Kp outbreak had different origins. These 9 isolates were partitioned into two clades according to genetic distance. Four plasmids, CP002474.1, CP006799.1, CP018455.1, and CP025459.1, were detected among the 9 isolates. The plasmid phylogeny and antibiotic resistance (AR) gene profile results were consistent with the sequencing results. We found that two clades of CP-Kp were responsible for this nosocomial outbreak and demonstrated the transmission route from two index patients. Plasmid carriage and phylogeny are a useful tool for identifying clades involved in disease transmission.